Knockout of the HaREase Gene Improves the Stability of dsRNA and Increases the Sensitivity of Helicoverpa armigera to Bacillus thuringiensis Toxin - Guan, Ruobing; Chen, Qiuyan; Li, Haichao; Hu, Shaoru; Miao, Xuexia; Wang, Guirong; Yang, Bin (Frontiers in Physiology, 2019)
Double-stranded RNA (dsRNA)-induced genes are usually related to RNA interference (RNAi) mechanisms and are involved in immune-related pathways. In a previous study, we found a lepidopteran-specific nuclease gene REase that was up-regulated by dsRNA and that affected RNAi efficiency in Asian corn borer (Ostrinia furnacalis). In this study, to verify the function of REase, the homologous gene HaREase in cotton bollworm (Helicoverpa armigera) was knocked out using CRISPR/Cas9 system. We found that the midgut epithelium structure was apparently not affected in the ΔHaREase mutant (Knock out: KO). Transcript sequencing results showed that most of the known insect immune-related genes were up-regulated in KO. When second instar larvae were fed artificial diet with Cry1Ac, a protoxin from Bacillus thuringiensis (Bt), in sublethal doses (2.5 or 4 μg/g), the growth rate of KO was repressed significantly. The dsRNA stability was also enhanced in midgut extraction of KO; however, RNAi efficiency was not obviously improved compared with the wild type (WT). The KO and WT were injected with dsEGFP (Enhanced green fluorescent protein) and subjected to transcriptome sequencing. The results showed that the expression levels of 14 nuclease genes were enhanced in KO after the dsRNA treatment. These findings revealed that HaREase expression level was not only related with dsRNA stability, but also with Bt resistance in cotton bollworm. When HaREase was knocked out, other immune- or nuclease-related genes were enhanced significantly. These results remind us that insect immune system is complex and pest control for cotton bollworm is an arduous task.